2014
DOI: 10.5194/isprsannals-ii-5-145-2014
|View full text |Cite
|
Sign up to set email alerts
|

Image pre-processing for optimizing automated photogrammetry performances

Abstract: ABSTRACT:The purpose of this paper is to analyze how optical pre-processing with polarizing filters and digital pre-processing with HDR imaging, may improve the automated 3D modeling pipeline based on SFM and Image Matching, with special emphasis on optically non-cooperative surfaces of shiny or dark materials. Because of the automatic detection of homologous points, the presence of highlights due to shiny materials, or nearly uniform dark patches produced by low reflectance materials, may produce erroneous ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 19 publications
1
36
0
5
Order By: Relevance
“…A number of previous researchers have suggested that the incorporation of HDR images in the photogrammetric pipeline would be advantageous for archaeological applications and would be worth more investigation (Wheatley, 2011;Ntregka, Georgopoulos, & Quintero, 2014;Guidi, Gonizzi, & Micoli, 2014). However, HDR imaging has not been frequently used in CH and in photogrammetry.…”
Section: Related Workmentioning
confidence: 99%
“…A number of previous researchers have suggested that the incorporation of HDR images in the photogrammetric pipeline would be advantageous for archaeological applications and would be worth more investigation (Wheatley, 2011;Ntregka, Georgopoulos, & Quintero, 2014;Guidi, Gonizzi, & Micoli, 2014). However, HDR imaging has not been frequently used in CH and in photogrammetry.…”
Section: Related Workmentioning
confidence: 99%
“…Research by Guidi [8], indicates that HDR fi les enables more tie points to be found. Agisoft does not allow the importing of HDR fi les, as generated by LadybugCapPro, so they need to be converted to the EXR format in Adobe Photoshop.…”
Section: The Impact Of the Format Of The Panoramasmentioning
confidence: 99%
“…Ntregka et al investigate the usage of HDR images in photogrammetric applications in the field of cultural heritage such as calibration and orthoimages (Ntregka et al, 2013). Guidi et al study the optical pre-processing with HDR imaging that may improve the automated 3D modeling pipeline based on SfM and image matching with special emphasis on optically non-cooperative surfaced of shiny and dark materials (Guidi et al, 2014). Another recent study uses HDR images in the 3D documentation of cultural heritage and investigates how HDR images affect the 3D models, geometrically through point clouds and radiometrically through textured models (Kontogianni and Georgopoulos, 2014).…”
Section: Hdr Imagingmentioning
confidence: 99%